Cajun country - Ancelet, Barry Jean 1951- (University Press of Mississippi, 1991)
Cajun culture, including "cooking, music, storytelling, architecture, arts and crafts, and festivals ... fishing, hunting, and trapping."
Includes bibliographical references and index
Origins -- Settlement and society -- Acadian folklife -- Family organization -- Religious rituals and festivals -- Folk medicine -- Folk law and justice -- Folk architecture -- Foodways -- Music and musical instruments -- Games and gaming -- Oral traditions
Keywords: Culture; Louisiana; Cajuns / Louisiana / Folklore; Cajuns / Louisiana / Social life and customs; Folklore / Louisiana; Material culture / Louisiana; Cajuns / Moeurs et coutumes; Alltag, Brauchtum; Louisiana / Social life and customs; Louisiane / Moeurs et coutumes